Interleukin-1 (IL-1) Receptor-Associated Kinase Leads to Activation of TAK1 by Inducing TAB2 Translocation in the IL-1 Signaling Pathway - Takaesu, Giichi (American Society for Microbiology, 2001)
Interleukin-1 (IL-1) is a proinflammatory cytokine that recognizes a surface receptor complex and generates multiple cellular responses. IL-1 stimulation activates the mitogen-activated protein kinase kinase kinase TAK1, which in turn mediates activation of c-Jun N-terminal kinase and NF-κB. TAB2 has previously been shown to interact with both TAK1 and TRAF6 and promote their association, thereby triggering subsequent IL-1 signaling events. The serine/threonine kinase IL-1 receptor-associated kinase (IRAK) also plays a role in IL-1 signaling, being recruited to the IL-1 receptor complex early in the signal cascade. In this report, we investigate the role of IRAK in the activation of TAK1. Genetic analysis reveals that IRAK is required for IL-1-induced activation of TAK1. We show that IL-1 stimulation induces the rapid but transient association of IRAK, TRAF6, TAB2, and TAK1. TAB2 is recruited to this complex following translocation from the membrane to the cytosol upon IL-1 stimulation. In IRAK-deficient cells, TAB2 translocation and its association with TRAF6 are abolished. These results suggest that IRAK regulates the redistribution of TAB2 upon IL-1 stimulation and facilitates the formation of a TRAF6-TAB2-TAK1 complex. Formation of this complex is an essential step in the activation of TAK1 in the IL-1 signaling pathway.